FORMULASI HUKUM PIDANA PADA UNDANG-UNDANG PERKAWINAN - Jhon Tyson Pelawi (Jurnal Education and Development, 2020)
Marriage according to religion and according to the State is an event that establishes a sacred relationship or a noble relationship to achieve the goals of a loving, loving, and giving offspring who become a baby for the survival of one's future. Marriage is also an event where religion regulates marriages that are in accordance with the Shari'a to get rewards for those who carry them out according to applicable regulations. Based on the description in the background of the problem, the problem in this study can be formulated, namely how the law enforcement of divorce cases due to acts of domestic violence. Law enforcement on divorce cases due to acts of violence in household can be applied criminal penalties to perpetrators who have been proven to do so so that justice and legal certainty in a decision can be achieved and the deterrent effect for perpetrators of domestic violence then divorce rates can be minimized